Mobilização de saberes profissionais para o ensino de literatura na licenciatura em letras: análise de um processo formativo - Gasparini, Nathália Luísa Giraud (Universidade do Vale do Rio dos Sinos, 2025)
This dissertation addresses initial teacher education for literature teaching. Its context is a formative process conducted in a Language and Literature course at a federal institute: a project in which two pre-service teachers studied works related to the perspective of literary literacy/literacies (Cosson, 2019; 2020; Amorim et al., 2022) and carried out reading workshops with elementary school students in a public school. The objective is to analyze how knowledge for teaching literature was mobilized, which included based on the representations of action constructed by the participants throughout this process, which included practical experiences, understood as activities that bring pre-service teachers closer to professional practice (Brasil, 2024). The study assumes that schools, as literacy agencies (Kleiman, 2006; 2007), are strategic spaces for promoting literary reading, and that such knowledge is part of teachers’ professional expertise. This involves the mobilization of professional knowledge in practical experiences, understood as activities that bring pre-service teachers closer to professional practice (Brasil, 2024). Following Tardif (2000; 2014), it is assumed that the mobilization of knowledge occurs when teachers select, translate, and elaborate knowledge in response to concrete situations, and according to Gatti (2014), this process involves an integration of ways of thinking and acting that goes beyond mere operational aspects. Data were generated through semi-structured interviews conducted before and after the workshops, as well as recordings of planning, discussion, and evaluation meetings. These discourses are examined based on the discursive consciousness (Tardif, 2000) of pre-service teachers taking as the unit of analysis the representations of action as proposed by Socio-Discursive Interactionism (Bronckart, 2006; 2010). The results provide evidence that the experience prompted processes of awareness that led participants to make sense of what was studied, while what was studied was, in turn, used to make sense of what occurred during the experience. The analysis of the meetings indicates that the planning and assessment activities conducted by the instructor—particularly when positive or insufficient courses of action were identified, and when learning objectives were established based on these assessments—played a significant role in this meaning-making process. Thus, the study of literary literacy/literacies proved to be a relevant contribution to the mobilization of knowledge, with literary reading as its central focus. In this process, the opportunities to plan and assess the work played a substantial role.
Keywords: Ensino de literatura; Formação inicial de professores; Licenciatura em Letras; Letramento literário; Mobilização de saberes profissionais; Literature teaching; Pre-service teacher education; Bachelor's degree in Portuguese and Literature; Literary literacy; Mobilization of professional knowledge; ACCNPQ::Lingüística, Letras e Artes::Lingüística